2018
DOI: 10.1536/ihj.16-595
|View full text |Cite
|
Sign up to set email alerts
|

Long Period and High Level of D-Dimer after Coronary Artery Bypass Grafting Surgery

Abstract: SummaryHyper-coagulation after off-pump coronary artery bypass grafting (OPCAB) is one of the main reasons for graft thrombosis. D-dimer is closely linked to the activation of coagulation. Few studies have reported the variation range and long-term abnormal coagulation after OPCAB in the Chinese population. Our study aimed to determine the characteristics and value of D-dimer after OPCAB.In this prospective study, 265 patients who underwent OPCAB for the first time were recruited from 2011 to 2012. The D-dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…18) Additionally, in human abdominal aortic aneurysm specimens, a strong and patch TNC staining was observed in the most dilated region of the aneurysm accompanied by severe tissue destruction. 19,20) Subsequently, elevated TNC expres-sion in aortic tissue released into blood, resulting in the elevated serum TNC levels. In addition, multiple logistic regression analysis revealed that serum TNC was an independent factor in predicting in-hospital death from acute AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Additionally, in human abdominal aortic aneurysm specimens, a strong and patch TNC staining was observed in the most dilated region of the aneurysm accompanied by severe tissue destruction. 19,20) Subsequently, elevated TNC expres-sion in aortic tissue released into blood, resulting in the elevated serum TNC levels. In addition, multiple logistic regression analysis revealed that serum TNC was an independent factor in predicting in-hospital death from acute AD.…”
Section: Discussionmentioning
confidence: 99%
“…DD is a small protein fragment that is the product of fibrin degradation after a blood clot degraded by fibrinolysis. 20) Previous studies demonstrated that DD was a good rule-out tool for acute AD, and acute AD would be excluded when DD levels were below 0.1 μg/mL with a sensitivity of 100%. 21) Recently, increased DD levels were observed in patients with type A acute AD, those who died during hospitalization, or those with severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer elevation may be seen in several diseases or situations. 6,7,21) Historically, a lack of specificity has been regarded as a disadvantage of D-dimer assessments; however, the low specificity has been transformed into an advantage in the evaluation of anticoagulation prognosis. In the current study, 3 patients died from heart failure, 1 patient died from cancer, and most of them (3/4) had abnormal D-dimer levels.…”
Section: D-dimer To Predict Outcomes In Post-mhvr Patientsmentioning
confidence: 99%
“…D-dimer, a product of cross-linked fibrin degradation, is only produced when both the blood coagulation and fibrinolytic pathways are concomitantly activated. 4,5) Elevated D-dimer levels are highly correlated with adverse clinical outcomes, including thrombotic or cardiovascular events and other severe conditions, [5][6][7] which cover most complications during oral anticoagulation therapy. 8) Previous studies reported that D-dimer exhibited a good prognostic value in patients with atrial fibrillation (AF) or cancer.…”
mentioning
confidence: 99%
“…Согласно имеющимся литературным данным, активация системы гемостаза после операции КШ влияет на вероятность неблагоприятных клинических исходов. В частности, более высокие уровни D-димера через месяц после КШ ассоциированы с рецидивом стенокардии [5]. B. Yanagawa и соавт.…”
Section: Introductionunclassified